A Most Distinguished Hungarian Scholar of Eugene O’Neill : In Memoriam Péter Egri (1932-2002) - Kurdi, Mária (FOCUS: Papers in English Literary and Cultural Studies, 2022)
Péter Egri (1932-2002) would have attained the age of ninety this year, has he not been, unfortunately, dead for twenty years. He became professor and chair of the English Department of Kossuth Lajos University, Debrecen, in the 1970s, then professor and for some years chair of the English Department in Eötvös Loránd University, Budapest. The range of his scholarly interests was both wide and far-reaching. Shortly after Egri’s untimely death Zoltán Abádi Nagy wrote “A Memorial Tribute,” which says: “Péter Egri, who excelled in English, Irish and American comparative studies and aesthetics, was a man of several careers in literature alone; with musical and fine arts history and aesthetics added, a combination emerged that was unique on the Hungarian scene of the past few decades” (10). The richness of Egri’s scholarly production is available in sixteen books, some edited volumes, over two hundred studies and essays, as well as shorter writings published in Hungary and in some other countries. In view of the scope of his achievement he can rightly be called a “scholar of comparative literary and cultural studies.” As such, he was both an Anglicist and an Americanist, who addressed works by William Shakespeare, Mark Twain, Stephen Crane, Aldous Huxley, J. M. Synge, G. B. Shaw, W. B. Yeats, T. S. Eliot, Eugene O’Neill, James Joyce, Samuel Beckett, Edward Albee, Tom Stoppard and others in his publications. At the beginning of his career, Egri also researched and wrote about modern Hungarian authors including Attila József and Tibor Déry.